Complications and management of Meckel's diverticulum - a review - Fa-Si-Oen, Patrick R.; Roumen, Rudi M. H.; Croiset van Uchelen, Fred A. A. M. (The European journal of surgery, 1999)
Objective: To review the anatomy, symptomatology, diagnosis, complications and management of symptomatic and asymptomatic Meckel's diverticula. Design: Retrospective study. Setting: Teaching hospital, The Netherlands. Subjects: 27 consecutive patients who underwent resection of a Meckel's diverticulum during the 16 year period 1 January 1981–31 August 1997. Main outcome measures: The symptomatology and histopathological findings. Results: 15 patients had symptoms and 12 did not. Haemorrhage and inflammation were the most common presenting symptoms. All histopathological signs of inflammation were found in those with symptomatic diverticula. Resected asymptomatic Meckel's diverticula were abnormal in only two occasions: one contained an adenocarcinoma and one a faecolith. Conclusion: All symptomatic Meckel's diverticula should be resected. The surgical treatment of asymptomatic Meckel's diverticula is still controversial. Copyright © 1999 Taylor and Francis Ltd.